Centralized Website Optimization at Modern Islamic Boarding School Baitussalam - Erman Agusta, Gino; Fatchul Arifin; Astriawati, Ningrum (International Journal of Community Service (IJCS), 2025)
Website today arises because of the increasingly high needs of the market and society in the field of technology. Pondok Pesantren Modern (PPM) Baitussalam has several education level units from kindergarten to high school level, including Integrated Islamic Kindergarten Baitussalam 1 Prambanan, Integrated Islamic Kindergarten Baitussalam 2 Cangkringan, Integrated Islamic Elementary School Baitussalam 1 Prambanan, Integrated Islamic Elementary School Baitussalam 2 Cangkringan, Integrated Islamic Junior High School Baitussalam Boarding School Prambanan, Integrated Islamic Junior High School Baitussalam Fullday School Cangkringan and Integrated Islamic Senior High School Baitussalam Boarding School Prambanan. Where the unit's website has not been fully centralized and several websites are not optimal. This training activity aims to integrate and optimize the website into a unified information. The method used is through training activities. Training activities use the method of lectures, questions and answers and mentoring. The result of this community service activity is that the centralized school website can integrate all education level units in PPM Baitusalam in disseminating information for teachers, female students and the general public; A centralized school website can optimize and make it easier for teachers, students and the general public to access information about the school or information about the world of education in general in one piece of information, besides that this centralized school website makes it easier for prospective students to register for all units in Pondok Pesantren Modern Baitussalam without the need to do it at school.